The effect of using silage of carrot pulp and hay with urea-added in dairy cow diets on milk yield and composition - رمضان تمام; وليد أحمد الرحمون; مهند جميل منى (Latakia University Journal -Biological Sciences Series, 2025)
The research was conducted at the Deir Hajar Station for Syrian Cattle Research in the Rural Damascus Governorate in 2022.The experiment lasted for 45 days, during which 8 homogeneous Holstein-Friesian cows, matched in age and production season, were randomly assigned to two groups:the control group T and the experimental group T1. The control group was fed a diet consisting of a concentrate, straw, and green fodder, while in T1, carrot pulp silage was substituted for part of diet with straw and urea based on dry matter at increasing ratios(8-16-24-32-40-48)%. The results showed that the produced silage had excellent specifications in terms of chemical composition, color, aroma, and pH level, which averaged 3.74±0.36. The silage was highly palatable for the cows, and no significant differences were recorded in dry matter, energy, and protein consumption between the two groups.Milk production was higher in the experimental group T1 at 4.92%, reaching 24.53 kg/day; however, this difference was not statistically significant.No significant differences were observed in the average milk fat percentage between the control group T and the experimental group T1, which were 3.22% and 3.59%, respectively.Similar results were obtained for protein and lactose percentages. Replacing carrot pulp silage with straw and urea as part of the diet reduced feed costs by 11.1% and decreased the cost of producing 1 kg of milk by 15.2%.Thus, the silage made from carrot pulp, straw, and urea exhibited good specifications, and increasing its dietary intake did not negatively impact dry matter consumption or milk production and composition while reducing feeding costs for milk production.